THE COST OF LAND USE REGULATION VERSUS THE VALUE OF INDIVIDUAL EXEMPTION: OREGON BALLOT MEASURES 37 AND 49. - HASCIC, IVAN; WU, JUNJIE (Contemporary Economic Policy, 2012)
This article presents an exploratory analysis of the effects of land use regulations on land values and land use patterns in a landscape near Eugene, Oregon. All land use regulations considered in this study, including exclusive farm use zoning, forest zoning, urban growth boundary designation, residential density zoning, commercial zoning, and industrial zoning, are found to affect land values and land use patterns both inside and outside of the designated zones. The framework is applied to measure the costs of the regulations versus the value of individual exemptions at the parcel level to illuminate the controversy surrounding Oregon Measures 37 and 49, which were passed to provide 'just compensation' for 'unfair regulatory burdens.' The cost of regulation is found to be lower than the value of an individual exemption for most regulations contested in the Measure 37 claims. However, governments tend to overregulate from the perspective of landowners. Although some land gained value under the six regulations and some lost value, the aggregate loss of land value was estimated to be several times larger than the gain. This does not necessarily mean that the governments overregulate from the perspective of society because land use regulations also generate public goods such as wildlife habitat and water quality protection. ( JEL K11, R15, R52)